Ontario Looking After Children (OnLAC) 2021 Provincial Report - Miller, Meagan (Université d'Ottawa | University of Ottawa, 2022)
This report contains data from the 2021 OnLAC year. This report is designed for use by child welfare organizations as a performance measurement system. The Assessment and Action Record (AAR) outcome data available in this report should assist child welfare organizations in the development of an internal evaluation program. The AAR findings are intended to help supervisors, program managers, executive directors and board members within child welfare organizations monitor children’s outcomes on a regular basis by comparing children’s and youths’ developmental progress with intended goals. A second intended use of the AAR is to inform decision-makers as to possible means of improving the quality and relevance of services on an ongoing basis. This report is also designed to provide policy-makers with accurate, up-to-date knowledge of system-wide outcomes thereby fulfilling an accountability function and a guiding function in identifying policies and practices that promote continuous improvements in child welfare policies and practices.
Keywords: child welfare; onlac; ontario looking after children; child development; outcome monitoring; ontario child welfare